Kekerasan permukaan semen ionomer kaca konvensional tipe II akibat lama penyimpanan (The surface hardness of type II conventional glass ionomer cement conventional because of the length of storage) - Asti Meizarini; Irmawati Irmawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Type II conventional glass-ionomer cements (GIC) are restorative materials consisting of powder and liquid mixed to produce a plastic mass that subsequently sets to a rigid solid. The early GIC was marketed without the expired date, although this material has been currently marketed with the expired date, how stable the materials are not yet clear. The purpose of this study was to evaluate the powder and the liquid GIC storage on the surface hardness of the samples. Six disc samples (5 mm in diameter and 3 mm thick) were made for each of four groups consisting of powder: aged liquid ages, aged powder: new liquid new, new powder new: new liquid new and aged powder: aged liquid ages respectively. All samples prepared followed the manufacturers’ recommendations and were allowed to set for 15 minutes then they were kept for 24 hours at room temperature before testing. Vickers microhardness was assessed for measuring the surface hardness at the top of the sample surface. The data were statistically analyzed using an ANOVA and LSD (p < 0.05). The results of this study indicated that the highest surface hardness was on the group of new powder: new liquid new = 52.040 VHN. The other groups were nearly similar, for new powder: aged liquid, aged powder: new liquid, aged powder: aged liquid they were 49.558 VHN; 49.123 VHN; 48.938 VHN respectively. Conclusion, powder and liquid of the type II conventional glass ionomer that had been stored for a long time descreased the surface hardness of the glass ionomer cements.